Galerie : 52 Werke der Kunsthalle Bielefeld. - Weisner, Ulrich; Kunsthalle Bielefeld (Bielefeld : Westfalen Verlag, 1986)
Archipenko, Alexander ; Baselitz, Georg ; Baumeister, Willi ; Beckmann, Max ; Böckstiegel, Peter August ; Calder, Alexander ; Cane, Louis ; Chagall, Marc ; Chia, Sandro ; Corinth, Lovis ; Delaunay, Sonia ; Ernst, Max ; Felixmüller, Conrad ; Freundlich, Otto ; González, Julio ; Heckel, Erich ; Hodler, Ferdinand ; Hoehme, Gerhard ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kiefer, Anselm ; Kirchner, Ernst Ludwig ; de Kooning, Willem ; Laurens, Henri ; Lipchitz, Jacques ; Maillol, Aristide ; Manguin, Henri-Charles ; Modersohn, Otto ; Moholy-Nagy, Laszlo ; Moore, Henry ; Mueller, Otrto ; Münter, Gabriele ; Nay, Ernst Wilhelm ; Noland, Kenneth ; Nolde, Emil ; Penck, A.R. ; Richier, Germaine ; Richter, Gerhard ; Rickey, George ; Rodin, Auguste ; Rohlfs, Christian ; Rückriem, Ulrich ; Schlemmer, Oskar ; Scott, Tim ; Serra, Richard ; Spagnulo, Giuseppe ; Stella, Frank ; Vogeler, Heinrich ; Zadkine, Ossip
geboortedatum per kunstenaar
Duits
boek